The Oldest Original Synagogue Building in the Diaspora: A Response to L. Michael White - Runesson, Anders 1968- (1999)
In 1997, the Harvard Theological Review published an article written by L. Michael White in which he “presents and analyzes evidence for the social location and organization of Jewish groups in the environs of Rome, specifically from the port city of Ostia” during the first centuries CE. White draws from two sources in his examination: archaeological remains of the Ostia synagogue and rather scanty—but important—epigraphical material, the Mindius Faustus and the Gaius Julius Justus inscriptions. White's study is the most extensive discussion of the archaeological evidence in English since the excavator, Maria Floriani Squarciapino, presented her preliminary reports from the excavations of the synagogue in the early 1960s. Despite the great interest that the synagogue at Ostia aroused when it was unearthed and excavated during two campaigns in 1961 and 1962, it has since been neglected by scholars.